b - Lunt, Pat. (b)
A complete six-year primary course which provides an engaging introduction to the key areas of Social Studies. It has been developed specifically for the Middle East and pays particular attention to the cultural requirements of the region. The course offers a structured syllabus covering citizenship, history, cultural studies, geography and PSHE.
Keywords: Social sciences -- Juvenile literature